A phase 2a trial investigating ninerafaxstat – a novel cardiac mitotrope for the treatment of diabetic cardiomyopathy (IMPROVE-DiCE). (3rd October 2022) - Hundertmark, M; Siu, A G; Matthews, V; Lewis, A J; Grist, J T; Patel, J; Chamberlin, P; Sarwar, R; Yavari, A; Frenneaux, M P; Valkovic, L; Miller, J J J J; et al.
Abstract: Background: Type 2 diabetes (T2D) is a significant, independent contributor to the development of heart failure (HF), driven by energetic, metabolic, structural and functional myocardial changes. The T2D heart is characterised by over-reliance on fatty acid utilisation, shows reduced glucose oxidation and inhibition of pyruvate dehydrogenase (PDH). This results in a diminished myocardial energy reserve and blunted adenosine triphosphate (ATP) generation as well as cardiac steatosis, contributing to lipotoxicity, and diastolic dysfunction. Purpose: We assessed the effects of ninerafaxstat – a novel cardiac mitotrope designed to shift myocardial substrate utilisation in favour of glucose and thus, restore myocardial energy homeostasis – on cardiac metabolism & diastolic function in patients with T2D and obesity. Methods: In this open-label, mechanistic phase 2a trial, we enrolled 21 patients with T2D & obesity (HbA1c median 7.0% (IQR 6.6, 7.8), weight 97kg (90, 102)) and subsequently treated them with 200mg ninerafaxstat twice daily for 4 or 8 weeks; (Fig. 1). Cardiac metabolism and function were assessed pre- & post-treatment using magnetic resonance imaging (MRI), 31P-, 1H- and, in a subset of n=9, hyperpolarized [1-13C]pyruvate MR spectroscopy. Results: T2D patients at baseline presented with impaired myocardial energetics with a markedly reduced PCr/ATP (1.6 [1.4, 2.1]), myocardial steatosis (myocardial triglycerides 2.2% [1.5, 3.2]) left ventricular (LV) hypertrophy (LV mass 130g [98, 152]), and diastolic dysfunction (peak diastolic strain rate 0.86 1/s [0.82, 1.06]). Ninerafaxstat significantly improved myocardial energetics (PCr/ATP median by 32%, p<0.01), reduced myocardial triglyceride content (by 34%, p=0.03) and improved LV diastolic function (peak circumferential diastolic strain rate by 10%, peak LV filling rate by 11%, both p<0.05) (Fig. 2). PDH flux was increased in 7/9 subjects (mean 45%, p=0.08), consistent with improved glucose utilisation. Left ventricular volumes and mass, heart rate and blood pressure remained unchanged. Conclusions: Treatment with ninerafaxstat significantly improves myocardial energetics, reduces myocardial steatosis and improves diastolic function in patients with T2D and obesity. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Imbria Pharmaaceuticals